Implementasi metode problem based learning dalam pembelajaran bahasa Arab maharah qiro’ah di MTs Tarbiyatul Banin Banat Tuban - Fachruddin, Mohammad Iqbal Rizky (Maliki Interdisciplinary Journal, 2024)
Arabic is a very important aspect of education, especially in Islamic educational institutions. Reading skills (maharah qiro'ah) are the main component in learning Arabic because this ability allows students to understand Arabic texts that are rich in information and knowledge. This research aims to determine the implementation of the Problem Based Learning (PBL) method in learning Arabic (maharah qiro'ah) at MTs Tarbiyatul Banin Banat Tuban. This research was conducted qualitatively using case studies to collect data through observation, interviews and documentation. The research results show that the Problem Based Learning (PBL) method is effective in improving students' reading skills, identifying problems that arise during the learning process, and providing alternative solutions to learning methods. Thus, it is hoped that learning Arabic (maharah qiro'ah) can be carried out well and achieve optimal results.